Taking charge of eczema self-management: a qualitative interview study with young people with eczema. Issue 1 (6th January 2021) - Greenwell, Kate; Ghio, Daniela; Muller, Ingrid; Roberts, Amanda; McNiven, Abigail; Lawton, Sandra; Santer, Miriam
Abstract : Objectives: To explore young people's experiences of eczema self-management and interacting with health professionals. Design: Secondary qualitative data analysis of data sets from two semistructured interview studies. Data were analysed using inductive thematic analysis. Setting: Participants were recruited from the UK primary care, dermatology departments and a community-based sample (eg, patient representative groups, social media). Participants: Data included 28 interviews with young people with eczema aged 13–25 years (mean age=19.5 years; 20 female). Results: Although topical treatments were generally perceived as effective, young people expressed doubts about their long-term effectiveness, and concerns around the safety and an over-reliance on topical corticosteroids. Participants welcomed the opportunity to take an active role in their eczema management, but new roles and responsibilities also came with initial apprehension and challenges, including communicating their treatment concerns and preferences with health professionals, feeling unprepared for transition to an adult clinic and obtaining treatments. Decisions regarding whether to engage in behaviours that would exacerbate their eczema (eg, irritants/triggers, scratching) were influenced by young people's beliefs regarding negative consequences of these behaviours, and perceived control over the behaviour and its negative consequences. Conclusions: Behavioural change interventions must address the treatment concerns of young people and equip them with the knowledge, skills and confidence to take an active role in their own eczema management.